Determinants of and Trends in Labor Force Participation of Women in Turkey - Dayıoğlu, Meltem; Kırdar, Murat G. (World Bank, Ankara, 2017)
Female labor force participation rate in Turkey is quite low by European Union (EU) and Organization for Economic Co-operation and Development (OECD) standards: it was 24.9 percent in 2006, compared to 66.1 percent in EU-27 and 60.8 percent in OECD countries. Moreover, it has declined from 34.3 percent in 1988 to 24.9 percent in 2006. The purpose of this report is to shed light on factors that determine women's participation in the labor market and the reasons behind the observed trends over the 1988-2006 periods. An important reason for the fall in female participation rate is urbanization. Turkey has witnessed high levels migration from rural to urban areas since 1988. The share of urban population rose from 51.1 percent in 1988 to 63.3 percent in 2006. Despite the declining trend, the female labor force participation rate in rural areas is still higher than that in urban areas, which has been more stable over time. In fact, the gender gap in participation rate in urban areas is much wider. Significant improvements have taken in place in women's schooling in recent decades in Turkey. The final interesting finding that requires further investigation is the low and stagnant participation rates of low skilled women - those with less than high school education. Over the 2000-2006 periods, the participation rate of low skilled women varied between 10.9 and 11.8 percent. These are considerably lower rates compared to that of low skilled men which, over the same time period, varied between 67.1 and 68.8 percent.